Upaya Membina Perilaku Peserta Didik Melalui Pembelajaran PAI di SMP Ikhlasiyah Palembang - Siti Zailiah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This article discusses Efforts to Foster Student Behavior Through PAI Learning at SMP Ikhlasiyah Palembang. This type of research is qualitative with a descriptive approach, data collection methods through observation, interviews and documentation. Data analysis techniques, namely starting from data collection, data presentation and drawing conclusions on the data obtained. While the technique of checking the validity of the data is through triangulation which consists of triangulation of time, sources and methods. From the results of the discussion that the efforts made by the school in fostering student behavior through PAI learning activities have been carried out well, the activities carried out include learning activities in PAI lessons and other activities namely reading the Koran, reading asmaul husna, praying dzuhur together, Commemoration of Islamic Holidays (PHBI), and Friday alms. All of these activities are routinely carried out in schools with the aim of fostering and instilling good character in students at SMP Ikhlasiyah Palembang.